2004
DOI: 10.1021/ar030160q
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Hydrogen Bond Motifs in Ligand Design:  The Role of Noncovalent Interactions in Metal Ion Mediated Activation of Dioxygen

Abstract: Hydrogen bonds influence secondary coordination spheres around metal ions in many proteins. To duplicate these features of molecular architecture in synthetic systems, urea-based ligands have have been developed that create rigid organic frameworks when bonded to metal ions. These frameworks position hydro-gen bond donors proximal to metal ion(s) to form specific chem-ical microenvironments. Iron(II) and manganese(II) complexes with constrained cavities activate O(2), yielding M(III) (M(III) = Fe and Mn) compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
274
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(282 citation statements)
references
References 69 publications
4
274
0
4
Order By: Relevance
“…1 Direct reaction of (L) with [Cu(NCCH 3 ) 4 ]BF 4 in CH 2 Cl 2 gives [Cu(L)NCCH 3 ]BF 4 (1) (Fig. 1) in 46% yield as an intense yellow-coloured powder, and was characterised by 1 H-NMR, MS and elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…1 Direct reaction of (L) with [Cu(NCCH 3 ) 4 ]BF 4 in CH 2 Cl 2 gives [Cu(L)NCCH 3 ]BF 4 (1) (Fig. 1) in 46% yield as an intense yellow-coloured powder, and was characterised by 1 H-NMR, MS and elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A recent proposal has suggested that in some cases H-bond(s) to the terminal oxo ligand could be used in stabilizing metal-oxo complexes. 18 The H-bonds would decrease the multiple bond character of the M-oxo unit, resulting in highspin complexes with longer M-O bondssproperties such as those found in [Fe III H 3 buea(O)] 2-. These predictions are consistent with the results presented here.…”
Section: Discussionmentioning
confidence: 99%
“…[9] We sought to utilize this self-organization by incorporating these tripodal scaffolds into a titanium-phosphonate material. The synthetic strategy is outlined in Scheme 1.…”
mentioning
confidence: 99%